Exploring long-term youth unemployment in Europe using sequence analysis: A reproducible notebook approach - Nikos Patias (REGION, 2019)
Youth unemployment~is a factor influencing European policy. The effects of financial crisis of 2008 in youth unemployment were prominent and varied across European countries and regions. This notebook aims to identify key representative trajectories of youth unemployment by NUTS 2 regions in Europe from 2008 to 2018. Moreover, this notebook provides a self-contained research workflow that is fully reproducible and transparent, using a wide range of functionalities offered by computational notebooks. The results show that there is a divide between northern and southern regions. Northern regions follow stable low youth unemployment levels, while southern regions follow stable high youth unemployment levels. Finally, the results show that there are patterns of regional inequalities between major metropolitan areas and their adjacent regions.
Keywords: 330; sequence analysis; unemployment; Europe; regional inequalities; reproducible research